2017
DOI: 10.11607/ofph.1803
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Protein Kinase A in Promoting Trigeminal Nociception in an In Vivo Model of Temporomandibular Disorders

Abstract: Aims To investigate cellular changes in the spinal trigeminal nucleus (STN) and trigeminal ganglion associated with trigeminal nociception mediated by inflammation in the temporomandibular joint (TMJ) capsule. Methods Sprague Dawley rats (n=86) were utilized to investigate cellular and behavioral responses to prolonged TMJ inflammation caused by bilateral injection of complete Freund’s adjuvant (CFA) in the capsule. To investigate the cellular effects of protein kinase A (PKA) in the STN, rats were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Immunohistochemistry and image analysis were conducted essentially as described in previous studies (Cady et al, 2011; Koop et al, 2017). Tissues were fixed in a solution of 4% paraformaldehyde overnight at 4°C, and cryoprotected by incubating tissues in 12.5% sucrose in distilled water at 4°C for one hour followed by 25% sucrose overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry and image analysis were conducted essentially as described in previous studies (Cady et al, 2011; Koop et al, 2017). Tissues were fixed in a solution of 4% paraformaldehyde overnight at 4°C, and cryoprotected by incubating tissues in 12.5% sucrose in distilled water at 4°C for one hour followed by 25% sucrose overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis of immunostaining data was performed essentially as described previously (Cornelison et al, 2016; Hawkins et al, 2015; Koop et al, 2017). The relative fluorescent staining intensity in spinal cord tissue was determined by measuring the grayscale intensity from four regions, in laminae I–III, of the medullary dorsal horn.…”
Section: Methodsmentioning
confidence: 99%
“…upregulation) [25][26][27] −  GFAP [28][29][30][31] − Release pro-inflammatory mediators [28] −  Gap junction function [28] − Increase neuronal activity (Nav1.7 and pNR1 upregulation) [28,30] o  Iba1/CD11b [32,33] o Release pro-inflammatory mediators [34] Carrageenan injection in the TMJ ND ND ND −  Iba1 [35] Zymosan injection in the TMJ ND ND ND − Iba1 [35] Capsaicin injection in the TMJ ND − S100B [36] − Gap junction function [36,37] ND ND − Release of inflammatory mediators [21] TMD CFA injection in the TMJ ND − GFAP [22][23][24] − Release pro-inflammatory mediators [22,25,26] − Gap junction function [22] −  neuronal activity (Nav1.7 upregulation) [25][26][27] −  GFAP [28][29][30][31] − Release pro-inflammatory mediators [28] −  Gap junction function [28] − Increase neuronal activity (Nav1.7 and pNR1 upregulation) [28,30] o  Iba1/CD11b [32,33] o Release pro-inflammatory mediators [34] Carrageenan injection in the TMJ ND ND ND −  Iba1 [35] Zymosan injection in the TMJ ND ND ND − Iba1 [35] Capsaicin inje...…”
Section: Headachementioning
confidence: 99%
“…− Not activated [42] Dental pulp injury − Release of inflammatory mediators [21] TMD CFA injection in the TMJ ND − GFAP [22][23][24] − Release pro-inflammatory mediators [22,25,26] − Gap junction function [22] −  neuronal activity (Nav1.7 upregulation) [25][26][27] −  GFAP [28][29][30][31] − Release pro-inflammatory mediators [28] −  Gap junction function [28] − Increase neuronal activity (Nav1.7 and pNR1 upregulation) [28,30] o  Iba1/CD11b [32,33] o Release pro-inflammatory mediators [34] Carrageenan injection in the TMJ ND ND ND −  Iba1 [35] Zymosan injection in the TMJ ND ND ND − Iba1 [35] Capsaicin injection in the TMJ ND − S100B [36] − Gap junction function [36,37] ND ND…”
Section: Headachementioning
confidence: 99%
“…TRPV1 and TRPA1 sensitization occurs through a mechanism involving multiple protein kinases, such as protein kinases C and A (PKC and PKA, respectively) and Ca 2+ /calmodulin dependent kinase II (CAMKII) ( 17 ). Elevated PKC, PKA, or CaMKII activity is associated with sensitization and activation in the nociceptive neurons ( 18 , 19 ). Numerous studies have reported that inflammation mediators can induce inconsistent activation of nociceptive neurons through G protein-coupled receptors (GPCRs) or receptor tyrosine kinases (RTKs) via cAMP/PKA, PLC/PKC, and CaMKII second messenger-signaling pathways ( 17 , 20 ).…”
Section: Nociceptive Neurons Sense the Tissue Microenvironmentmentioning
confidence: 99%